Saccharomyces cerevisiae Dbf4 Has Unique Fold Necessary for Interaction with Rad53 Kinase - Matthews, Lindsay A. (American Society for Biochemistry and Molecular Biology, 2012)
Dbf4 is a conserved eukaryotic protein that functions as the regulatory subunit of the Dbf4-dependent kinase (DDK) complex. DDK plays essential roles in DNA replication initiation and checkpoint activation. During the replication checkpoint, Saccharomyces cerevisiae Dbf4 is phosphorylated in a Rad53-dependent manner, and this, in turn, inhibits initiation of replication at late origins. We have determined the minimal region of Dbf4 required for the interaction with the checkpoint kinase Rad53 and solved its crystal structure. The core of this fragment of Dbf4 folds as a BRCT domain, but it includes an additional N-terminal helix unique to Dbf4. Mutation of the residues that anchor this helix to the domain core abolish the interaction between Dbf4 and Rad53, indicating that this helix is an integral element of the domain. The structure also reveals that previously characterized Dbf4 mutants with checkpoint phenotypes destabilize the domain, indicating that its structural integrity is essential for the interaction with Rad53. Collectively, these results allow us to propose a model for the association between Dbf4 and Rad53.